Differences of Subjective Well-Being in European Long-term Care Regimes - Fekete, Márta; Patyán, László; Hüse, Lajos; Huszti, Éva; Takács, Péter (European Journal of Mental Health, 2022)
Introduction: With the increase of life expectancy, the issue of quality of life (QoL) for the elderly is getting more focus. Beside the individual view, social and economic aspects are becoming more pronounced. Aims: In this study, we set out to establish a new classification of long-term care (LTC) regimes by examining the relationship between care systems and subjective quality of life. Methods: Our work was based on data from the Survey of Health, Ageing and Retirement in Europe through a secondary analysis of CASP-12 results. It was assumed that higher quality of life values could be observed in countries providing a higher standard of social care. We studied the background variables in different LTC regimes. Results: The data shows that the development and availability of care systems have a significant indirect correlation with older people’s subjective well-being. Our results raise the possibility of a new subdivision of care regimes. Conclusions: Those countries featured earlier as family-based systems and Central-Eastern European countries were growing closer to each other in this classification. As our statistical method proved, family-based and Central-Eastern European regimes are not significantly different (Minimisers). Northern countries, where investment and quality of life are also high, remain highly positioned on the scale (Maximisers). Countries that have medium-level investments and subjective well-being parameters place in the middle of the scale (Optimisers). Global changes (climate, migration, political culture, technology) are expected to have an effect on social care regimes, especially on Minimisers, where the realization or failure of investments is a critical question.